14 chủ đề tiếng Anh môn nói : Luyện thi chứng chỉ A - B - C / Nguyễn Hữu Dự - Nguyễn, Hữu Dự
Sample talks, Model sentences, questions and answers, supplementary questions, commonly - sentence patterns